2022
DOI: 10.3390/ijms232012653
|View full text |Cite
|
Sign up to set email alerts
|

The Central Nervous Mechanism of Stress-Promoting Cancer Progression

Abstract: Evidence shows that stress can promote the occurrence and development of tumors. In recent years, many studies have shown that stress-related hormones or peripheral neurotransmitters can promote the proliferation, survival, and angiogenesis of tumor cells and impair the body’s immune response, causing tumor cells to escape the “surveillance” of the immune system. However, the perception of stress occurs in the central nervous system (CNS) and the role of the central nervous system in tumor progression is still… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 143 publications
0
3
0
Order By: Relevance
“…These patterns have been consistently documented in the scientific literature with studies positing that increased sympathetic drive underlies this abnormal activity of the ANS [ 13 , 18 , 19 , 20 ]. Previous studies have suggested that the heightened sympathetic drive promotes tumorigenesis, which was supported by observations of augmented innervation of sympathetic nerve fibers in tumors in addition to higher levels of circulating adrenergic catecholamines [ 32 , 33 ]. Increased inflammation and oxidative stress are also proposed drivers of cancer-related abnormal ANS activity [ 32 ].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…These patterns have been consistently documented in the scientific literature with studies positing that increased sympathetic drive underlies this abnormal activity of the ANS [ 13 , 18 , 19 , 20 ]. Previous studies have suggested that the heightened sympathetic drive promotes tumorigenesis, which was supported by observations of augmented innervation of sympathetic nerve fibers in tumors in addition to higher levels of circulating adrenergic catecholamines [ 32 , 33 ]. Increased inflammation and oxidative stress are also proposed drivers of cancer-related abnormal ANS activity [ 32 ].…”
Section: Discussionmentioning
confidence: 88%
“…Previous studies have suggested that the heightened sympathetic drive promotes tumorigenesis, which was supported by observations of augmented innervation of sympathetic nerve fibers in tumors in addition to higher levels of circulating adrenergic catecholamines [ 32 , 33 ]. Increased inflammation and oxidative stress are also proposed drivers of cancer-related abnormal ANS activity [ 32 ]. While other studies observed reduced HRV among cancer patients, the current study possesses several novelties that strengthen and expand upon the existing scientific evidence.…”
Section: Discussionmentioning
confidence: 88%
“…Em outro estudo, foi evidenciado que a ansiedade exerce um efeito negativo no prognóstico e no tratamento de pacientes com câncer, sendo relatada a maior probabilidade de ter comorbidades de ansiedade do que pessoas saudáveis. (HONG et al, 2022) Como já foi citado antes, o estresse se tornou parte da vida moderna, o que o tornou uma preocupação significativa, pois pode ser um fator de risco para diversas doenças, como o câncer. O estresse crônico pode ser causado por um ritmo de vida acelerado, uma alta carga de trabalho e pressão profissional, problemas econômicos, isolamento social, pressões culturais e outras preocupações da vida moderna.…”
Section: ) Abordagem Diagnóstica Em Grupos Específicosunclassified
“…Chronic stress has been shown to affect the effectiveness of anticancer treatments by exerting an influence on the TME ( Hong et al, 2022 ). The SNS plays a role in the formation of pre-metastatic niches ( Ieguchi et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%